Yakutski nfectious hospital in the years of the Great Patriotic War - S. S. Sleptsova; S. S. Sleptsov; M. N. Andreev; S. E. Zhulljarova (Журнал инфектологии)
Based on archival materials, the activity of the Yakutsk infectious diseases’ hospital and its employees during the years of World War II are reviewed. Besides fulfilling their professional duties, medical workers carried out active educational work among the population and acted in measures to clean up the city and improve the infectious diseases hospital. The work also contains biographical information about V.M. Anaskin, the first chief physician of the hospital, who made an invaluable contribution to the work of this medical institution.